Weightlifting clean-and-jerk techniques: gender-specific biomechanics analysis - Nopin, S. V.; Koryagina, Y. V.; Ter-Akopov, G. N.; Abutalimova, S. M (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze the gender-specific biomechanics of the modern weightlifting clean-and-jerk techniques.